Decision usefulness of goodwill reported under IFRS - Tonny Stenheim (Copenhagen Business School (CBS), 2012)
The dissertation investigates the decision usefulness of goodwill-accounting numbers. Theory and methodology from value relevance, earnings-management and corporate-governance literature are employed in order to investigate the decision usefulness. The dissertation compares the value relevance of goodwill reported under the impairment-only method (current IFRS) with the value relevance of goodwill reported under alternative accounting methods. It also investigates the extent to which goodwill-impairment losses under IFRS are associated with variables for economic impairment and/or earnings-management incentives. And finally, it investigates whether an estimate of misrepresentation of economic impairment in goodwill is associated with earnings-management incentives and/or corporate-governance mechanisms. The results suggest that the impairment-only method provides accounting numbers that more faithfully depict economic fundamentals as reflected in stock prices. The results also suggest that reported goodwill-impairment losses are not strongly affected by earnings-management incentives. Still, misrepresentation of economic impairment in goodwill does not seem to be constrained by corporate-governance mechanisms. In overall, these findings support the recently implemented impairment-only method under current IFRS
hdl:10398/8398
Keywords: 650